2016
DOI: 10.1089/sur.2013.134
|View full text |Cite
|
Sign up to set email alerts
|

Infection in Burns

Abstract: Background: Developments in critical care and surgical approaches to treating burn wounds, together with newer antimicrobial treatments, have significantly reduced the morbidity and mortality rates associated with this injury. Methods: Review of the pertinent English-language literature. Results: Several resistant organisms have emerged as the maleficent cause of invasive infection in burn patients, including methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus, Pseudomonas, Acinetoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
158
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(204 citation statements)
references
References 41 publications
2
158
2
12
Order By: Relevance
“…A study using HSE models has shown that reduced expression of filaggrin protein resulted in increased epidermal S. aureus colonization . S. aureus is also a major pathogen in skin infections in burn wound patients, and large efforts are made to prevent and treat wound infections . The expectation is that many studies will investigate the role of micro‐organisms in skin diseases and therapeutic strategies to treat these conditions.…”
Section: The Skin Microbiome: a Novel Player In Skin Barrier Researchmentioning
confidence: 99%
“…A study using HSE models has shown that reduced expression of filaggrin protein resulted in increased epidermal S. aureus colonization . S. aureus is also a major pathogen in skin infections in burn wound patients, and large efforts are made to prevent and treat wound infections . The expectation is that many studies will investigate the role of micro‐organisms in skin diseases and therapeutic strategies to treat these conditions.…”
Section: The Skin Microbiome: a Novel Player In Skin Barrier Researchmentioning
confidence: 99%
“…(CRE), Pseudomonas spp ., non-albicans Candida spp. , and Aspergillus spp ., have been associated with increased mortality after burns 52,53 . Most of these strains have nosocomial origins, can spread within burn units, and be very difficult to eradicate.…”
Section: State Of the Sciencementioning
confidence: 99%
“…Most of these strains have nosocomial origins, can spread within burn units, and be very difficult to eradicate. Although a new generation of antimicrobial agents is being developed 52,54 , it is often necessary to use agents with high chemical toxicity, such as chlorhexidine gluconate, which may impede wound healing while controlling wound infection.…”
Section: State Of the Sciencementioning
confidence: 99%
“…Thus, as similar to the above discussed for DFUs, laboratory engineered materials had been developed to fulfill the need for alternative strategies for wound covering and tissue regeneration in these patients (Ulrich, 2014). Furthermore, the control/prevention of nosocomial infections in burn patients is a pivotal factor for reducing hospital stays and morbidity (Norbury et al, 2016).…”
Section: Burns and Tissue Engineeringmentioning
confidence: 99%